Wilbur Ross and the Bank of Ireland - Rosenthal, Jean W., 1945- ([London] : SAGE, 2016)
In August 2011, Wilbur Ross, an American investor whose firm, WL Ross & Co LLC, specialized in distressed and bankrupt companies, was part of a group that raised $1.6 billion to purchase 35% of the Bank of Ireland. Even for Ross, known for his ability to find value in properties that other investors had shunned, investing in an Irish bank seemed risky. Ireland had grown rapidly in the late 1990s and early 2000s, but had experienced a massive contraction beginning in 2008. Stabilizing the banks required a succession of government interventions and finally a bailout from the International Monetary Fund, the European Central Bank, and the European Commission. In early 2013, Ross's investment seemed successful. But problems remained. This case study discusses this topic.
Originally Published in: Rosenthal, J. W., Walsh, E., Spiegel, M., Goetzmann, W., Bach, D., McLoughlin, D. P.,. Elias, J. (2013). Wilbur Ross and the Bank of Ireland. 103-13. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/bank-ireland.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Bank of Ireland; Bank management -- Case studies; Organizational change -- Case studies; Consolidation and merger of corporations -- Case studies; Investments -- Case studies